Perfusion of the iris after selective laser trabeculoplasty: optical coherent tomography angiography data - D. S. Maltsev; A. A. Kazak; A. N. Kulikov; A. S. Vasilyev; M. A. Burnasheva (Российский офтальмологический журнал)
Purpose: to study iris perfusion in patients with primary open-angle glaucoma (POAG) after selective laser trabeculoplasty (SLT) using optical coherence tomography angiography (OCTA).Material and methods. 12 patients aged 68.3 ± 8.4 with stage I to III POAG underwent a standard ophthalmic examination as well as OCTA examination of the iris, which was performed through the center of the pupil under photopic conditions using RTVue-XR with Angio Retina 3-mm protocol. All patients received examination before SLT, one day, seven days, and 30 days after SLT. Vascularity was determined with ImageJ as the total length of binarized and skeletonized vessels over the full thickness of the iris slab.Results. A statistically significant correlation was found between the values of intraocular pressure (IOP) measured one month after SLT and iris vascularity before SLT, one day after SLT, and their difference. The strongest correlation (r = 0.60, p = 0.001) was found between iris vascularity one day after SLT and IOP one month after the procedure.Conclusions. SLT is accompanied by an increase in iris vascularity, which fact may probably be used in the prediction of the final IOP in these patients.